Odpowiedzi

2010-02-22T15:50:05+01:00
A)x+x-1=3
x=2
spr.4-1=3

b)2x-x+4,5=8,5
x=4
spr. 8-4+4,5=8,5

c)2(2x+1)=8
x=1,5
spr.6+2=8

d)x+(3x-5)=7
x=3
spr.12-5=7

e)3x-(x+5)=-1
x=2
spr. 6-2-5=-1

f)2(x+1)-4x=1
x=0,5
spr. 1+2-2=1

g)2(x+3)=18
x=6
spr.12+6=18

h)x+3(x-2)=-22
x=-4
spr.-4-12-6=-22

i)5x-2(x+3)=9
x=5
spr.25-10-6=9

j)4(2x+3)-5x=-3
3x+12=-3
x=-5
spr. -40+12 + 25=-3

k)2(x+1)+5x=16
x=2
spr. 4+2+10=16

l)-4x-3(2x+1)=7
-10x-3=7
x=-1
spr. 4+6-3=7


Liczę na naj
Najlepsza Odpowiedź!
2010-02-22T15:51:23+01:00
A)x+x-1=3
2x=2 /:2
x=1
1+1+1=3
b)2x-x+4,5=8,5
x=8,5-4,5
x=4
8-4+4,5=8,5
c)2(2x+1)=8
4x+2=8
4x=6 /:4
x=6/4=3/2= 1 1/2
d)x+(3x-5)=7
x+3x-5=7
4x=12 /:4
x=3
e)3x-(x+5)=-1
3x-x-5=-1
2x=4 /:2
x=2
f)2(x+1)-4x=1
2x+2-4x=1
-2x=-1 /:(-2)
x=1/2
g)2(x+3)=18
2x+6=18
2x=12 /:2
x=6
h)x+3(x-2)=-22
x+3x-6=-22
4x=-16 /:4
x=-4
i)5x-2(x+3)=9
5x-2x-6=9
3x=15 /:3
x=5
j)4(2x+3)-5x=-3
8x+12-5x=-3
3x=-18 /:3
x=-6
k)2(x+1)+5x=16
2x+2+5x=16
7x=14 /:7
x=2
l)-4x-3(2x+1)=7
-4x-6x-3=7
-10x=10 /:-10
x=-1

Mam nadzieje, że pomogłam
Pozdrawiam!!!